Potassium sorbate and sodium benzoate as preservatives in candied kondol - Fandialan,Agnes M.; Guzman, Matilde P. (1968.)
Five hundred grams each of candied kondol were dipped for two minutes in two times their weight 2, 3, and 5% solutions of potassium sorbate and of sodium benzoate. Analyses were made on total plate count, yeast and mold count, total sugars, percent moisture, residual concentration of sorbic acid and pH. These tests were done on the first and third weeks of storage. Results of the objective tests showed that the amount of preservatives absorbed by the sample was the most important factor in retarding mold growth. Low moisture, low pH and high sugar concentration supplemented the activity of the preservatives. On the third week of storage, the untreated sample had visible mold growth while the treated samples showed mold growth only on the sixth week.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Food preservatives; Fruit -- Preservation